Dynamical analysis of a fractional-order avian-human influenza epidemic model with logistic growth for avian population. (October 2020) - Ye, Xingyang; Lin, Shimin; Xu, Chuanju
In this paper, a fractional order avian-human influenza epidemic model with logistic growth for avian population is investigated. The dynamical behavior of this model is discussed. We first establish the existence, uniqueness, non-negativity and positive invariance of the solution. Then we analyze the existence of various equilibrium points, and some sufficient conditions are derived to ensure the global asymptotic stability of the disease free equilibrium point and endemic equilibrium point. Finally, we take some numerical simulations to validate the analytical results.